"Sistema de análisis estadístico para un banco de datos entomológico" - Onofre Wong, Kevin Manuel (2019)
In the State Technical University of Quevedo (UTEQ) several studies have been developed on the insects of the area, especially on the area of forestry research, these study processes are carried out individually by each researcher, the same as They use different ways to collect data which generates files with abundant records. In order to have a data bank where all the studies carried out, a web and mobile application has been developed that offers entomological data management for statistical analysis. A database was designed that supports the variables required in entomological research. The development has been carried out within the agile methodology "Unified Rational Process" (RUP), for its high level of abstraction which means that it motivates the use of reusable concepts such as frameworks. Microsoft SQL Server Analysis Services 13.0.4 was used as a data mining tool, because it provides client libraries (AMO 10.0.0, ADOMD.NET 10.5.0) which were used to integrate in the ASP.NET web application the creation of analysis databases and models of data. mining. The construction of the application was carried out under Microsoft's .Net framework 4.5.2, as a C # 5.0 programming language, in an ASP.NET web environment using form web pages, data access through the Entity Framework 6.1.3 and as a SQL Server 13.0.4 database engine. On the other hand, Mantnet.numers 4.5.1 was used for correlation calculations, geolocation was implemented with Opencagedata 1.0.0 and leaflet 1.3.4 JavaScript library for interactive maps. Keywords: Geolocation, statistics, mining, entomological, data enriched.